STATISTICAL STUDIES REGARDING THERAPEUTIC APPROACHES FOR EDENTULOUS SOCIAL CLINICAL CASES IN STUDENTS`PRACTICAL STAGES - Magda-Ecaterina Antohe; Monica Andronache; Ramona Feier; Ovidiu Stamatin; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2017)
The variety of clinical cases met by the practitioner is a very important element in the choice of particularities for the development of partially removable prosthetic structures. Aim:The purpose of this study is materialized by the quantification of incidence and prevalence of edentation and its complications in social pacients, with an emphasis on establishing the relationship between the general state of the patient, the environmental factors and the clinical and biological indices. Material and method:A large group of patients was selected and studied in a group of 68 patients - 36 women and 32 men, coming from the urban area 54.55% and 45.45% from the rural area, who were examined and treated for a period of two years (2015-2017) at Clinical Base of the Faculty of Dental Medicine - UMF "Gr. T. Popa" Iasi. Results:The most common situation was that of the Kennedy 1 class - found in 33% of cases, followed by Kennedy's second grade (17%) and grade III (14%). A comparable percentage of patients (10%) had a Kennedy 4th grade, and the lowest incidences were recorded for edentation classes V and VI (14% and 12% respectively).Conclusions :Each clinical case is having a possible ideal therapeutical solution based on a complex algorithm of conception, selection and materialization